COMT inhibition with tolcapone in the treatment algorithm of patients with Parkinson’s disease (PD): relevance for motor and non-motor features - Antonini, Angelo (Dove Medical Press, 2008)
Levodopa is the most effective treatment in Parkinson’s disease and the association with COMT inhibitors widens its plasma bioavailability and effectiveness. Tolcapone is a potent COMT inhibitor whose utilization in PD is limited due to safety concerns on liver toxicity. However, recent data indicate that if liver function is actively monitored, tolerability is no worse than other currently available therapies. By contrast, administration of tolcapone is associated with significant clinical improvement and benefit involves also non-motor features. In this review we discuss the rationale for the use of tolcapone in association with levodopa and other treatments in PD, and we provide an indirect comparison of current strategies to reduce “off” time. We propose that future guidelines include a trial with tolcapone in all PD patients who continue to complain about motor fluctuations despite treatment with entacapone and/or MAO-B inhibitors. Moreover, we suggest that tolcapone should be considered before surgical or infusional strategies are applied.